Checklist of Fishes at Selected Rivers around Bukit Merah Reservoir, Perak, Malaysia - Nurul Fazlinda Mohd Fadzil; Amir Shah Ruddin Md Sah; Mohd Shafiq Zakeyuddin; Zarul Hazrin Hashim; Mohd Syaiful Mohammad; Khalid Puteh (Tropical Life Sciences Research, 2016)
A study was conducted at five selected rivers around Bukit Merah Reservoir, Perak, Malaysia for eight weeks in order to determine the fish diversity and distribution. A total of 28 species comprised of 9 families were identified. The study depicted that there were significant changes to the fish composition when compared to previous study which had captured 36 species due to different areas covered and different types of sampling gear used between both studies.